To find \( f(-4) \) for the function \( f(x) = 2x^2 + 7x + 18 \), we will substitute \(-4\) into the function:
\[ f(-4) = 2(-4)^2 + 7(-4) + 18 \]
Now, calculate each term step by step:
-
Calculate \((-4)^2\): \[ (-4)^2 = 16 \]
-
Now multiply by 2: \[ 2 \times 16 = 32 \]
-
Calculate \(7(-4)\): \[ 7 \times -4 = -28 \]
-
Now substitute these values into the expression: \[ f(-4) = 32 - 28 + 18 \]
-
Combine the constants: \[ 32 - 28 = 4 \] \[ 4 + 18 = 22 \]
So, we find that: \[ f(-4) = 22 \]
Thus, the final answer is: \[ \boxed{22} \]